Managing disaster preparedness for institution of Higher Learning: an exploratory study in Perlis - Muhammad Shahar, Jusoh; Azuddin, Bahari, Lt Kol (B); Evawaynie Valquis, Md. Isa (Universiti Utara Malaysia (UUM), 2008)
Organized by Universiti Utara Malaysia (UUM), 18th - 19th August 2007 at Legend Hotel, Kuala Lumpur.